A long-term survivor of undifferentiated carcinoma of the liver successfully treated with surgical treatments: A case report and literature review. (2018) - Hiraki, Masatsugu; Kitahara, Kenji; Miyoshi, Atsushi; Koga, Hiroki; Nakamura, Hiroaki; Kubo, Hiroshi; Ikeda, Osamu; Yoshioka, Wataru; Nakashita, Shunya; Nishihara, Yunosuke; Akashi, Michiaki; Azama, Shinya; et al.
Highlights: Undifferentiated carcinoma of the liver is extremely rare disease. We experienced a long-term survivor of undifferentiated carcinoma of the liver successfully treated with radical hepatectomy. The tumor showed a huge hypovascular cystic mass with ring enhancement and partial solid component. It might grow quickly and show necrosis at the center of the tumor, making it difficult to distinguish from liver abscess. This disease has markedly different clinical and biological features from common primary malignant tumor of the liver. Abstract: Introduction: Undifferentiated carcinoma of the liver is extremely rare. The biological characteristics and standard strategy for its treatment have not been established yet. Presentation of case: A 45-year-old man was admitted because of fever elevation and shivering. Abdominal computed tomography revealed a hypovascular cystic mass in segments 6 and 7 of the liver measuring 11.5 × 9.0 cm with ring enhancement and partial solid component. A diagnosis of liver abscess was made, and percutaneous transhepatic abscess drainage was performed. Reddish brown-colored pus showed no bacteria or amoebas. However, cytology demonstrated malignant cells. After additional examinations of magnetic resonance imaging and the positron emission tomography, extended posterior sectionectomy with cholecystectomy was performed. The excised specimen showed a solid and irregular tumor with extensive central necrosis. A pathological examination revealed diffuse proliferation of oval- and spindle-shaped malignant cells. Immunohistochemically, the malignant cells were diffusely positive for AE1/AE3 and vimentin and focally positive for granulocyte colony-stimulating factor and cytokeratin 19; however, hepatocyte-specific antigen, glypican 3, cytokeratin 7, and CD56 were negative. Therefore, a diagnosis of undifferentiated carcinoma of the liver was made. He has remained well without any recurrence for three years since the operation. Discussion: Undifferentiated carcinoma of the liver might grow rapidly, resulting in necrosis with a cystic component. Therefore, it can be difficult to distinguish from liver abscess. Conclusion: This disease has markedly different clinical and biological features from common primary malignant tumor of the liver. However, if the tumor is a solitary mass, surgical resection might lead to a good prognosis.